2006
DOI: 10.1128/iai.74.5.2659-2666.2006
|View full text |Cite
|
Sign up to set email alerts
|

LfhA, a Novel Factor H-Binding Protein of Leptospira interrogans

Abstract: The early phase of leptospiral infection is characterized by the presence of live organisms in the blood. Pathogenic Leptospira interrogans is resistant to the alternative pathway of complement mediated-killing, while nonpathogenic members of the genus are not. Consistent with that observation, only pathogenic leptospires bound factor H, a host fluid-phase regulator of the alternative complement pathway. Ligand affinity blot analyses revealed that pathogenic L. interrogans produces at least two factor H-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
0
23

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(179 citation statements)
references
References 58 publications
4
152
0
23
Order By: Relevance
“…62 Leptospiral binding proteins to C4BP, factor H, and factor H-like have been identified in Leptospira. 17,18,46,[63][64][65][66] We report that Lsa23 is a novel C4BP and factor H binding protein of Leptospira, although with the ligand affinity for factor H binding protein seems to be low.…”
Section: Discussionmentioning
confidence: 99%
“…62 Leptospiral binding proteins to C4BP, factor H, and factor H-like have been identified in Leptospira. 17,18,46,[63][64][65][66] We report that Lsa23 is a novel C4BP and factor H binding protein of Leptospira, although with the ligand affinity for factor H binding protein seems to be low.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, fH-binding proteins have been identified in Leptospira interrogans (31), West Nile virus (32), and Neisseria meningitidis (33). We have shown that N. gonorrhoeae evades complement killing by using its Por molecules to bind HufH (6).…”
mentioning
confidence: 94%
“…To escape complement, many pathogens use the deposition of complement inhibition molecules, such as factor H, on their membranes. Verma et al (6) described a Leptospira interrogans molecule that can bind to factor H (LfhA) avoiding complement activation. In addition, it was shown that human serum opsonization of pathogenic leptospires increased the adherence to neutrophils via the complement component C3 receptor (CR3) instead of K.A.…”
Section: Introductionmentioning
confidence: 99%